A detailed nonuniform thermal model of a parabolic trough solar receiver with two halves and two inactive ends. (February 2015) - Cheng, Ze-Dong; He, Ya-Ling; Qiu, Yu
Abstract: In this paper a detailed one dimensional nonuniform thermal model of a parabolic trough solar collector/receiver is presented. The entire receiver is divided into two linear halves and two inactive ends for the nonuniform solar radiation, heat transfers and fluid dynamics. Different solar radiation and heat transfer modes can be taken into consideration for these four different regions respectively. This enables the study of different design parameters, material properties, operating conditions, fluid flow and heat transfer performance for the corresponding regions or the whole receiver. Then the nonuniform model and the corresponding uniform thermal model are validated with known performance of an existing parabolic trough solar collector/receiver. For applications, the uniform thermal model can be used to quickly compute the integral heat transfer performance of the whole PTC system while the nonuniform thermal model can be used to analyze the local nonuniform solar radiation and heat transfer performance characteristics and nonuniform heat transfer enhancements or optimizations. Later, it could also be effectively used with an intelligent optimization, such as the genetic algorithm or the particle swarm optimization, to quickly evaluate and optimize the characteristics and performance of PTCs under series of nonuniform conditions in detail. Highlights: A detailed one dimensional nonuniform/uniform thermal model of a PTC is developed. Different solar radiation and heat transfer modes are modeled for different regions. The nonuniform model and the corresponding uniform thermal model are well validated. The uniform model can quickly compute the integral heat transfer performance of PTC. The nonuniform model can analyze local nonuniform solar radiation and heat transfers.